2014
DOI: 10.1007/jhep04(2014)041
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Rényi entropy for CFT with W symmetry

Abstract: In this paper we investigate the holographic Rényi entropy of two disjoint intervals on complex plane with small cross ratio x for conformal field theory with W symmetry in the ground state, which could be dual to a higher spin AdS 3 gravity. We focus on the cases of W 3 and W 4 symmetries. In order to see the nontrivial contributions from the W fields, we calculate the Rényi entropy in the expansion of x to order x 8 in both the gravity and the CFT sides. In the gravity side the classical contributions to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
114
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(125 citation statements)
references
References 51 publications
7
114
2
2
Order By: Relevance
“…After that, one can obtain the short-interval expansion of the Rényi entropy by evaluating the corresponding one-point or multi-point functions of the OPE blocks. This trick has been adopted to calculate the Rényi entropy for some special cases [11][12][13][14][15][16][17][18][19][20], such as the Rényi entropy of two intervals on complex plane and of the one-interval on torus. In this paper, we adopt the same trick to investigate the short-interval expansion of excited state Rényi entropy on a cylinder, and then compare our results with the thermal state Rényi entropy.…”
Section: Jhep11(2016)116mentioning
confidence: 99%
“…After that, one can obtain the short-interval expansion of the Rényi entropy by evaluating the corresponding one-point or multi-point functions of the OPE blocks. This trick has been adopted to calculate the Rényi entropy for some special cases [11][12][13][14][15][16][17][18][19][20], such as the Rényi entropy of two intervals on complex plane and of the one-interval on torus. In this paper, we adopt the same trick to investigate the short-interval expansion of excited state Rényi entropy on a cylinder, and then compare our results with the thermal state Rényi entropy.…”
Section: Jhep11(2016)116mentioning
confidence: 99%
“…This leads to the proof of the RyuTakayanagi formula for the holographic entanglement entropy [23,24]. More interestingly, from the study on the Rényi entropy of double intervals with a small cross-ratio and the single interval on a torus [25][26][27][28][29][30][31][32][33][34], it turns out that the holographic computation is even correct at 1-loop level. It is found that the c 0 order contribution to the Rényi entropy from…”
Section: Jhep12(2015)109mentioning
confidence: 99%
“…Another is to the case of higher spin gravity, which is the case that we focus on here, in particular its 3d version and corresponding 2d CFT dual. The study of entanglement entropy in higher spin theories was initiated in [7,8] and further work appears in [9][10][11][12][13][14][15][16][17]. Our two main goals are the following: first to attempt to derive from first principles the prescriptions advanced in [7,8], 1 and second to extend these considerations to the case of Rényi entropy in higher spin theories.…”
Section: Jhep07(2015)168 1 Introductionmentioning
confidence: 99%